Influence of pre-slaughter handling on stress responses, fresh and frozen pork quality, tenderness and sensory attributes - Banisetty, Dr. Sonia; E, Dr E. Naga Mallika; Allada, Dr A. Udaya Kiran (The Indian Journal of Animal Sciences, 2026)
Pre-slaughter handling conditions exert a decisive influence on pork quality through modulation of physiological stress responses and post-mortem muscle metabolism. The present study evaluated the effects of standard handling, stressful handling and good management practices (GMP) on stress indicators, post-mortem pH decline, fresh and frozen pork quality, tenderness, oxidative stability and sensory attributes under Indian commercial conditions. Sixty market-weight pigs were allotted to three pre-slaughter handling treatments. Stress was assessed through behavioural indicators and serum cortisol concentration. Longissimus dorsi muscle samples were analysed for pH (45 min and 24 h), water-holding capacity, myofibrillar fragmentation index (MFI), Warner–Bratzler shear force (WBSF), lipid oxidation (TBARS), freeze–thaw loss and frozen storage stability up to 90 days at −18 °C. Sensory evaluation of fresh and frozen–thawed pork was conducted by a trained panel. Stressful handling significantly elevated cortisol concentration, accelerated post-mortem pH decline, reduced water-holding capacity, increased oxidative deterioration and lowered tenderness and sensory acceptability (p < 0.05). In contrast, GMP effectively minimized physiological stress, maintained desirable pH patterns and improved both fresh and frozen pork quality. The findings demonstrate that adoption of good pre-slaughter management practices is a practical, cost-effective and welfare-friendly strategy to enhance pork quality and frozen storage stability.